MOLECULAR CHARACTERIZATION OF OLIVE CULTIVARS IN IRAQ USING AFLP MARKERS - Mohammed, Iqbal; Mohammed, Ali; Al-Awadei, Salwa; Khierallah, Hussam (Iraqi Journal of Science, 2024)
Amplified fragment length polymorphism (AFLP) analysis was used to study the genotype relation among ten different olives varieties from al- zafrania and al-mosel station ministry of agriculture/Iraq Shami, Sorani, Manzanilla ,Kaissy, Arbequine ,Jlot, Baaskika ,Dahkan, Nabali, Khodeir , Nine primers combinations were used which produced about 250 amplified fragment. . One hundred and forty fife of these loci (59.8%) were polymorphic over all the genotypes tested. Dendrogram and matrix of similarity were obtained by the Unweighted Pair-GroupMethod analysis (UPGMA).study showed four group 1 : Jlot , Dahkan , Kiassy, Basskika 2 : Manzanilla, Khodeiri, Sorani, 3 : Nabali, Arbequine 4 : Shami . AFLP has a powerful tool for detecting genetic relationship among cultivars , and help in known the pedigree of relatives and ancestors .Key word : Olive , PCR , AFLP , Molecular Markers ,